ANALISIS PERBANDINGAN PEMERIKSAAN HEMOGLOBIN MENGGUNAKAN ALAT HB METER DENGAN ALAT SPEKTROFOTOMETER PADA IBU HAMIL - Sri Wahyuni Gayatri; Irna Diyana Kartika; Asrini Safitri (Universitas Islam Negeri Alauddin Makassar, 2022)
The prevalence of anemia in Indonesia according to the World Health Organization (WHO) in 2021 in pregnant women is 57.1%. Anemia in pregnant women can cause postpartum hemorrhage which is the cause of death in childbirth. International Committee for Standardization in Haematology (ICSH) recommends checking hemoglobin levels using the cyanmet-hemoglobin method. This method is easy to do because it has a standard and can measure all types of hemoglobin. The purpose of this study was to determine the comparison of hemoglobin levels using the Hb Meter and Spectrophotometer for pregnant women. The research design used was prospective with a descriptive analytic method with a Cross Sectional approach. Hemoglobin examination with a spectrophotometer has lower results than using a Hb Meter and is significantly significant. Conclusion: Examination of hemoglobin with a spectrophotometer has lower results than using an Hb meter and is significantly significant.